2021
DOI: 10.1038/s41591-021-01369-8
|View full text |Cite
|
Sign up to set email alerts
|

A trial of gantenerumab or solanezumab in dominantly inherited Alzheimer’s disease

Abstract: Code availabilityAll code for data cleaning and analysis associated with the current submission is available upon request to the corresponding author and is provided as part of the replication package.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
232
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 245 publications
(239 citation statements)
references
References 58 publications
5
232
0
2
Order By: Relevance
“…In support of the concept of a need for earlier intervention of Aβ therapeutics, the effect of gantenerumab on plaque reduction and downstream biomarkers of tau pathology and neuronal injury appeared to be larger in the asymptomatic group vs. the symptomatic group-though the small number of participants limited the statistical power of these findings. Although no cognitive or clinical benefit was observed, these findings suggest that removal of amyloid plaques may be a viable strategy in preventing or slowing the biological progression of AD if introduced at an optimal time [43].…”
Section: Review Of Amyloid Prevention Approachesmentioning
confidence: 72%
“…In support of the concept of a need for earlier intervention of Aβ therapeutics, the effect of gantenerumab on plaque reduction and downstream biomarkers of tau pathology and neuronal injury appeared to be larger in the asymptomatic group vs. the symptomatic group-though the small number of participants limited the statistical power of these findings. Although no cognitive or clinical benefit was observed, these findings suggest that removal of amyloid plaques may be a viable strategy in preventing or slowing the biological progression of AD if introduced at an optimal time [43].…”
Section: Review Of Amyloid Prevention Approachesmentioning
confidence: 72%
“…Dental anxiety was also identified as a major barrier to accessing dental treatment for people with ID [ 31 ]. Mentally challenged individuals tend to be less cooperative than the regular patient and dentists experience more difficulty in managing them during treatment sessions [ 32 ]. Friendly encounters with dental professionals during SO-SS events may contribute to enhance the dental compliance of SO athletes.…”
Section: Discussionmentioning
confidence: 99%
“…On the 21st June 2021, results from a randomized, placebo-controlled, multi-arm trial of gantenerumab or solanezumab in participants with dominantly inherited AD (DIAD) across asymptomatic and symptomatic disease stages were disclosed. Despite both drugs demonstrated convincing Aβ target engagement, gantenerumab failed to show a beneficial effect on cognitive measures, whereas solanezumab-treated group even exhibited a greater cognitive decline on some measures compared to placebo [9]. One week later, a cross sectional study conducted on 598 amyloid-positive participants patients was published and revealed that soluble Aβ 42 levels above 800 pg/ml were correlated with normal cognition irrespective of (and despite increasing) brain amyloid burden, implying that increasing soluble Aβ 42 , rather than reducing Aβ plaques, might represent a better therapeutic option [11].…”
Section: Discussionmentioning
confidence: 92%